Seeking refuge in South Africa: The victimization of vulnerable persons - James Chadley (Temida, 2017)
Many Africans confront and deal with very trying situations in their countries that are very different from the comforts enjoyed in developed parts of the world. Labeled as a ‘traumatized continent’ (Norridge, 2013: 64), many Africans motivated by the basic human necessities for food and safety flee their countries, seeking refuge in South Africa. The large influx of refugees has given rise to invalid concerns from the government and the ‘champions’ of their interest (Mauss, 1975: 10), the media. These concerns have spurred changes in the practice of the asylum system which are aimed at targeting refugees, rather than improving their situation, increasing the vulnerability of persons already fleeing persecution: the refugees, the victims. The aim of this paper is to analyze the problem from a victimological stand point, and draw attention to the issue that more research needs to be conducted with victims to improve our understanding of the impacts these practices have.